Constitutional protection of the right to education in Tanzania and South Africa : a comparative study - Benneh, Emmanueal Yaw (University of Pretoria, 2011)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2010.